The short American century : a postmortem - Bacevich, Andrew J. (Harvard University Press, 2012)
Declares "the American century", the name Henry Luce gave to an era of American prosperity beginning in 1941, dead, and collects essays explaining what the American century was and meant, and why many believe it has met a premature demise.